Restråstoff i blå og grønne verdikjeder i Møre og Romsdal – status og mulige bruksområder innen mat, fôr og gjødsel - Løes, Anne-Kristin; Bergslid, Ildri (Rose) Kristine; Hareide, Nils-Roar; Kjerstad, Margareth; Midtbø, Lisa Kolden; Friis Pedersen, Susanne; Sæter, Lovise (Norwegian Centre for Organic Agriculture (NORSØK), 2020)
This report describes the output of investigations made by researchers in Møreforsking, Runde Environmental Centre and Norwegian Centre for Organic Agriculture (NORSØK) to map the types and amounts of residual raw materials from the green and blue value chains in Møre and Romsdal county. In this county, located on the NW coast of Norway, fishery (and aquaculture) is a very important industry, but the county also has a significant agricultural sector, dominated by grassland and dairy cows. The blue and green value chains are highly different, and the report gives a brief description of how fishery of wild fish and dairy production are carried out in this county by 2020, to better understand the residual raw materials which are, or may become, available from these sectors. The Norwegian bioeconomy comprises both blue and green value chains. The blue value chain comprises seafood and other products being harvested or raised in the ocean; or raised in water on shore. The green value chain comprises food, wood, fibre and possibly other products being grown or harvested on land. In this report, the blue value chain is restricted to wild, captured fish and shellfish from the sea, hence not including aquaculture. The reason is that in the aquaculture sector, except for the sludge comprised of fish faeces and feed losses, residual raw materials are generally managed very carefully with efficient use of all materials. Further, residual materials from wild fish are easier to integrate as fertilisers in organic growing, which is of high interest for NORSØK. For the green value chain, we have not included residual materials from wood or fibre, with the exception that wool from sheep is included since this material is closely linked to the production of meat and is currently often poorly utilised. We used information about enterprises from a public register (Brønnøysund) to describe the two value chains by means of the number of enterprises in relevant sectors. All enterprises have a code describing their type of commercial ...